Edukasi berlogika di era digital bagi masyarakat - Yoppy Mirza Maulana (Universitas Pendidikan Indonesia (UPI), 2022)
Thinking is a mental activity to compile an idea in making a conclusion. One of the thinking skills that is always considered in a person's life in acting is the ability to think logically. Thinking logically or logically is a thinking activity that is in accordance with reason, rational or reasonable, which results in correct decisions. In this digital era, it is very easy to interact with other people with social media. However, interacting with other people requires good thinking and logic so that it can provide good actions. In the digital era, it is also easier to receive abundant information, but how to choose that information so that there are no logical fallacy. Therefore, the purpose of this community service is to educate the public in terms of logic in the digital era from three perspectives, namely the perspective of biopsychology, psychology, and logic. The learning method is lecture, discussion, question and answer, and it is done online. Based on the results of feedback from participants, that the usefulness of this education got an average score of 30.5% and very good 62.5%, meaning that it adds insight for participants. Besides being useful, this education can also provide solutions to improve thinking and logic, this is done during the interaction between speakers and participants. During the interaction, they discussed real case studies such as computer repair service employees in completing computer repair services and students when planning further studies. The case study solution uses a lateral thinking model approach with the support of mind map software.